The brides of the big valley : [large type] 3 romances from a unique Pennsylvania Amish community - Brunstetter, Wanda E.; Brunstetter, Jean; Brunstetter, Richelle (Center Point Large Print, 2019)
Journey to a unique area of Pennsylvania where three distinct Amish communities thrive, and meet three young women whose struggles with faith, family, and romance will touch your heart.